Factors influencing adherence to clinical guidelines in the management of cancer‐associated thrombosis. (20th October 2016) - Mahé, I.; Chidiac, J.; Helfer, H.; Noble, S.
Abstract : Summary: International academic and regulatory guidelines consistently recommend the long‐term use of low‐molecular‐weight heparins (LMWHs) as the standard for the treatment of cancer‐associated thrombosis (CAT). However, both physicians and patients are reluctant to follow established guidelines. Insufficient compliance with treatment recommendations among care physicians represents a loss of opportunity for patients at very high risk of recurrence of venous thromboembolism (VTE) and death. Few data are available regarding adherence to CAT clinical practice guidelines. Based on published data, we aimed to review the gap between guidelines and practice to draw a more precise picture of current practice in order to precisely identify the extent to which patient management is currently lacking with respect to treatment guidelines. Published observational studies, registries and surveys on cancer‐associated VTE treatment were reviewed. In spite of evidence from randomized controlled trials (RCTs) showing the usefulness of long‐term LMWH, only approximately 50% of patients are managed according to established guideline recommendations. Patient profiles and co‐morbidities influence compliance with standard guidelines. A better knowledge of physician and patient‐related factors that influence therapeutic decisions may improve the implementation of clinical practice guidelines. Efficient awareness programs including a multidisciplinary approach are necessary to implement guidelines aimed at optimizing the therapeutic management of cancer‐associated VTE.